Indikasi Kecurangan Laporan Keuangan pada Perusahaan Manufaktur Periode 2022-2024 - Yola Yolanda; Robinhot Gultom (Universitas Methodist Indonesia, 2025)
This research aims to examine and analyze the effect of financial target, financial stability, nature of industry, change of auditor, change of director on financial statement fraud using the Beneish M-Score at manufacture companies listed in Indonesia Stock Exchange period 2022-2024. The population in this study are 296 companies. The sampling method used was purposive sampling and obtained 97 companies as research samples. The data analysis method used is logistic regression analysis and interaction regression analysis using the SPSS version 26. The results of the analysis show that simultaneously the financial target, financial stability, nature of industry, change of auditor, and change of director influence fraudulent financial statement. Partially, financial stability and nature of industry influence fraudulent financial statement, while financial target, change of auditor and change of director have no effect on fraudulent financial statement.